PROBLEMS ON SFG THEMATIC PROGRESSION IN ESL ACADEMIC WRITING - Heri Kuswoyo; Susardi Susardi (Leksema: Jurnal Bahasa dan Sastra, 2017)
The objective of this research is to identify the problems on the thematic progression in fifth semester students’ academic writing. It examines the problems caused by the misuse of theme and rheme in the thematic progression of their writing. The data in this research are taken from 20 pieces of fifth semester students’ academic writing. The collected data are analyzed based on the theory of problem in thematic progression, regarding misuse of theme and rheme put forward by Bloor & Bloor (1992) and Arunsirot (2013). Then, descriptive qualitative and library research methods are applied in this research. The results of the research reveal that six problems in thematic progression are found; they are the problem of brand new theme, the problem of double rheme, the problem of empty rheme, the problem of empty theme, the problem of overuse of constant theme pattern and the problem of confusing selection of textual theme. In addition, other four new problems are also identified. They are the problem of incomplete clause, the problem of error in choosing topical theme, the problem of unneeded textual theme, and the problem of double textual theme. In conclusion, the students must be aware of the flow of theme and rheme of thematic progression in their writing.